Facilitating the comprehension of theoretical frameworks during distant learning. A research on methodological approaches (Journal of Educational Sciences, 2021)
To increase the level of education at distance learning, it is necessary to use such modified learning concepts, that would improve the perception of not only theoretical material, but also allow students to consolidate the knowledge they had into action. That is why researchers here attempt to identify the most effective method of information perception by students. The effectiveness of the illustration technique, and the amazing power of the human perception system did mostly serve us as motivational factors for choosing audiovisual tools, namely video tutorials, as a visualization method. Since the vi- sualization method is one of the key tools of information perception, this study would help to assess the importance of video lessons in pedagogical practice not only as one of the widely used methods of material transfer in the modern world, but also as an effective way to improve the cognitive potential of students in the study of polytechnic subjects. But video tutorials are not the only method of training in this research which were used for selected focus group. The survey conducted at the end of the study will allow researchers to either draw a conclusion about the effectiveness of video lessons as a method of transmitting material and learning in conditions of remotely education, or to suggest alternative methods to improve the perception of the material by students.Key words: video tutorials, video content, distance learning, form, technology, audiovisual learning tools, visualization, cognitive potential, analogy method.